A Numerical approach of activation energy and gyrotactic effects on MHD Carreau Nanofluid flow over plate, wedge and stagnation point - Varatharaj K.; Tamizharasi R. (Case Studies in Thermal Engineering, 2024)
This study numerically investigates the steady two-dimensional flow of a Carreau nanofluid with activation energy and motile microorganisms over a plate, wedge and stagnation point. The effects of the magnetic field, the Brownian motion, the viscous dissipation and the thermophoresis examined for both shear-thinning and the shear-thickening fluids. The similarity transformations are implemented to convert the governing equations into a non-dimensional form for easier analysis. The Runge–Kutta Method and the shooting technique are employed for finding numerical solutions using MATLAB plot form. The obtained numerical results were analyzed for a broad spectrum of dimensionless parameters and are discussed through graphs. These encompass 0.1≤M≤0.4,0.2≤We≤0.8,0.1≤S≤0.4,0.1≤Ec≤0.4,5≤Sc≤20,0.01≤R≤0.04,1≤Nb≤4,0.1≤Nt≤0.4,0.1≤Pe≤0.4,0.01≤Pr≤2and 1≤Ec≤2.5. These ranges were explored concerning velocity, temperature, concentration, diffusion, wall frictional factor and heat transfer rate, both through numerical computations and graphical representations. A decreasing trend in profiles is observed except for velocity, as the magnetic field parameter increases. The flow over a plate exhibits lower skin friction, heat transfer, mass transfer and gyrotactic microorganism compared to other geometries. The Brownian motion leads to a decreased nanoparticle concentration and motile microorganism density, while increasing thermophoresis has the opposite effect. The suction/injection parameter increases fluid velocity but decreases the temperature, the concentration and the motile microorganism density. The shear-thinning nanofluids demonstrate higher rates of the heat transfer, the mass transfer and the motile microorganism compared to shear-thickening fluids. Furthermore, the present analysis demonstrates that as the Peclet number and bioconvective Schmidt number increase, there is a corresponding decrease in microorganism concentration. Additionally, the higher activation energy E is found to enhance the concentration field due to the reduced chemical reaction rates.